Islamic Capital Market Integration in 5 ASEAN Countries in the Covid-19 Era - Muhammad Ryan Romadhon; Siti Mutmainah (Universitas Airlangga, 2023)
ABSTRACT The purpose of this study was to analyze the short-term and long-term relationship between the Islamic capital markets of 5 selected countries in the Covid-19 era. This study used a quantitative approach using weekly secondary data from January 2020 to December 2022. The data analysis model used Vector Auto Regression (VAR) analysis. The results of this study show that in the short term, variants in the capital market will change due to shocks in other ASEAN Islamic capital markets, but short-term deviations in the Islamic capital market will adjust in the long term. meanwhile, in the long run, Islamic capital markets in ASEAN countries that were tested, have integrated despite the occurrence of a health crisis that also has an impact on the financial crisis. This provides an opportunity for investors to mitigate risks and increase profit margins, especially in Islamic stock exchanges in ASEAN countries. On the other hand, this research allows investors to reformulate a more diversified portfolio after the Covid-19 pandemic. Keywords: Integration, Islamic Capital Market, ASEAN, Covid 19 ABSTRAK Tujuan dari penelitian ini adalah untuk menganalisis hubungan jangka pendek dan jangka panjang antara pasar modal syariah 5 negara terpilih di era Covid-19. Penelitian ini menggunakan pendekatan kuantitatif dengan menggunakan data sekunder mingguan januari 2020 sampai dengan desember 2022. Model analisis data menggunakan analisis Vector Auto Regression (VAR). Hasil penelitian ini menunjukkan bahwa dalam jangka pendek, varian di pasar modal akan berubah karena guncangan di pasar modal syariah ASEAN lainnya, namun penyimpangan jangka pendek di pasar modal syariah akan menyesuaikan dalam jangka panjang. sementara dalam jangka panjang, pasar modal syariah di negara-negara ASEAN yang teruji, memiliki integrasi meskipun terjadi krisis kesehatan yang juga berdampak pada krisis keuangan. Hal ini memberikan suatu kesempatan bagi para investor untuk memitigasi risiko dan memperbesar margin keuntungan terutama di bursa saham syariah negara ASEAN. Disisi lain, dengan adanya penelitian ini memungkinkan membantu para investor untuk merumuskan kembali portofolio yang lebih terdiversifikasi setelah terjadinya pandemi covid-19. Kata Kunci: Integrasi, Pasar Modal Syariah, ASEAN, Covid 19 REFERENCES Abd. Majid, M. S. (2018). Who Co-Moves The Islamic Stock Market of Indonesia -The US, The UK, or Japan? Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 10(2), 267–284. doi:10.15408/aiq.v10i2.7288 Abdul Karim, B., & Abdul-Rahman, A. (2020). Market integration in asean-5: Evidence of Islamic and conventional stock markets. Polish Journal of Management Studies, 21(1), 186–198. doi:10.17512/pjms.2020.21.1.14 Abdulkarim, F. M., Akinlaso, M. I., Hamid, B. A., & Ali, H. S. (2020). The nexus between oil price and Islamic stock markets in Africa: A wavelet and Multivariate-GARCH approach. Borsa Istanbul Review, 20(2), 108–120. doi:10.1016/j.bir.2019.11.001 Ahmed, F. (2021). Assessment of Capital Market Efficiency in COVID-19. European Journal of Business and Management Research, 6(3), 42–46. doi:10.24018/ejbmr.2021.6.3.839 Awwal, M. A. F. (2021). The corona pandemic on sharia capital market in Indonesia. Iqtishoduna, 10(2), 95–104. doi:10.36835/iqtishoduna.v10i2.864 Aziz, A., Rachmat, N., Abu, A., Adnan, Y., Islam, M. H., Islam, U., Hasan, Z., & Indonesia, G. (2020). Does integration superpower stock market for index of sharia stock in Indonesia. International Journal of Management Science and Business Research, 9(10), 170–177. doi:10.5281/zenodo.4990752 Bekaert, G., Harvey, C. R., & Ng, A. (2005). Market integtation and cintagration. The Journal of Business, 78(1), 39-70. doi:10.1086/426519 Cahyaningrum, A., & Robiyanto, R. (2021). Pengujian integrasi pasar modal di Kawasan Asia sebelum dan selama pandemi Covid-19. Jurnal Akuntansi Keuangan Dan Bisnis, 14(2), 211–220. doi:10.35143/jakb.v14i2.4673 Chen, M. P., Lee, C. C., Lin, Y. H., & Chen, W. Y. (2018). Did the S.A.R.S. epidemic weaken the integration of Asian stock markets? Evidence from smooth time-varying cointegration analysis. Economic Research, 31(1), 908–926. doi:10.1080/1331677X.2018.1456354 Chen, N. F., Roll, R., & Ross, S. A. (1986). Economic Forces and the Stock Market. Journal of Bussiness, 59(3), 383–403. Climent, F., & Meneu, V. (2003). Has 1997 Asian crisis increased information flows between international markets. International Review of Economics & Finance, 12(1), 111–143. doi:10.1016/s1059-0560(02)00140-5 Dantes, R. (2019). Wawasan pasar modal syariah. Ponorogo: Wade Group. Elmizan, G. H., Rahmawati, V., & Talim, A. (2022). Understanding and interest in sharia capital market investment of PTKIN and PTKIS Students. Indonesisan Interdisciplinary Journal of Sharia Economics, 5(2), 441–458. doi:10.31538/iijse.v5i2.2165 Erdo, S., Gedikli, A., & Ismail, E. (2020). Volatility spillover effects between Islamic stock markets and exchange rates